2017
DOI: 10.1371/journal.pone.0172527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HLA class I, HLA class II and KIRs on vertical transmission and chronicity of hepatitis C virus in children

Abstract: Background & aimThere is evidence that maternal viral load of HCV during delivery influences the risk for Mother-to-child transmission (MTCT), but this does not explain all cases. We study the role of the immunogenetic profile (HLA, KIRs and KIR-ligand binding) of mothers and children in HCV-MTCT and in chronicity in the children.Methodology79 HCV-RNA (+) mothers and their 98 children were included. 24 children were infected, becoming chronic in 8 cases and clearing in 16. HLA-class-I and II and KIRs were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Specifically, Ruiz-Extremera et al . found that the children of mothers with KIR3DS1 had a higher risk of HCV chronicity than the children of mothers without this receptor (75% and 19%, respectively) 24 . In our study, the presence of the KIR3DS1 receptor was also linked with chronic HCV infection, showing a higher frequency in patients who had chronic HCV infections (86.2%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, Ruiz-Extremera et al . found that the children of mothers with KIR3DS1 had a higher risk of HCV chronicity than the children of mothers without this receptor (75% and 19%, respectively) 24 . In our study, the presence of the KIR3DS1 receptor was also linked with chronic HCV infection, showing a higher frequency in patients who had chronic HCV infections (86.2%).…”
Section: Discussionmentioning
confidence: 97%
“…also found that KIR2DS3 was the principal gene related to HCV viral persistence 16 . A study of risk for mother-to-child transmission of HCV found that KIR3DS1 was associated with development of chronic HCV infection 24 . Specifically, Ruiz-Extremera et al .…”
Section: Discussionmentioning
confidence: 99%
“…In China, approximately 40 million individuals are infected with hepatitis C virus (HCV), and it is estimated that 50%–to 85% have developed CHC, while 20%–30% of these patients will progress to liver cirrhosis that may lead to hepatocellular carcinoma (J. Li & Zhuang, ). Up to now, the mechanism of CHC and its haematological progress is not clear; however, the host immune system genes, such as human leucocyte antigen (HLA) genes, and their killer‐cell immunoglobulin‐like receptors (KIR) genes could play a role in HCV clearance and the development of CHC (Marangon et al, ; Mozer‐Lisewska et al, ; Ruiz‐Extremera et al, ; Sung et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…human leucocyte antigen (HLA) genes, and their killer-cell immunoglobulin-like receptors (KIR) genes could play a role in HCV clearance and the development of CHC (Marangon et al, 2011;Mozer-Lisewska et al, 2016;Ruiz-Extremera et al, 2017;Sung et al, 2011).…”
mentioning
confidence: 99%
“…HLA-mismatch between a mother and her child has been described as favorable with regard to vertical viral transmission, since the child´s immune cells has better chance to recognize and kill the virus if its immune system is different from its mother's. HLA-mismatch and the presence of certain HLA-types have been shown to reduce the rate of vertical transmission of HCV-VT, but the findings are contradicting (43,135,136). It has been demonstrated that maternal neutralizing HCVantibodies are not protective of HCV-VT (137,138).…”
Section: 24( Other(host(immune(factors(and(vertical(transmission(mentioning
confidence: 99%